Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.eclinm.2021.100963
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy for HIV controllers: Reasons for initiation and outcomes in the French ANRS-CO21 CODEX cohort

Abstract: Background Less than 1% of Human Immunodeficiency Virus (HIV)-infected individuals are able to achieve spontaneous viral control without requiring antiretroviral therapy (ART). Whether these HIV controllers (HIC) are at risk of HIV-associated comorbidities and could benefit from ART is debated, but recent studies reported decreased T -cell activation upon ART initiation. We report the frequency of ART initiation, reasons to treat, treatment outcome on immunovirological p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…This is a matter of debate, as international recommendations claim for an early introduction of ART in PLWH. HICs might start therapy for 2 main reasons: mainly a decline in the CD4 levels (independently of viral control loss) or viral control loss [ 29 , 40 ]. We had already shown that clinical events leading to CD4 decline were scarcely reported [ 29 ] and mainly consisted of nonsevere infections, as reported in our current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a matter of debate, as international recommendations claim for an early introduction of ART in PLWH. HICs might start therapy for 2 main reasons: mainly a decline in the CD4 levels (independently of viral control loss) or viral control loss [ 29 , 40 ]. We had already shown that clinical events leading to CD4 decline were scarcely reported [ 29 ] and mainly consisted of nonsevere infections, as reported in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…We had already shown that clinical events leading to CD4 decline were scarcely reported [ 29 ] and mainly consisted of nonsevere infections, as reported in our current study. However, studies analyzing the effect of ART in HICs have mainly shown an effect on the HIV VL and immune activation parameters, but data on CD4 T-cell counts or CD4:CD8 ratio normalization remain controversial [ 20 , 40 ]. Furthermore, the impact of ART on reducing the risk of nADEs beyond improvement in inflammatory biomarkers has not been firmly proven.…”
Section: Discussionmentioning
confidence: 99%
“… 44 These findings point to the probable coexistence of different mechanisms of HIV persistence (clonal amplification and ongoing replication) in EC, VC and treated subjects and further support that ART may provide and additional layer of protection to some EC, by further reducing the level of residual HIV replication and ongoing viral evolution. 45 , 46 , 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…People with HIV who have low or undetectable HIV RNA levels without taking ART (“elite controllers”) have elevated levels of inflammation that are reduced after ART is initiated . In addition, even those who manifest low viral loads initially often do not maintain control over time . Based on the theoretical benefits of reducing inflammation in people with HIV, treating elite controllers is reasonable.…”
Section: Initiation Of Artmentioning
confidence: 99%